2017
DOI: 10.1080/00016357.2017.1406614
|View full text |Cite
|
Sign up to set email alerts
|

X-ray microtomography assessment of Carisolv and Papacarie effect on dentin mineral density and amount of removed tissue

Abstract: There was higher DMD, more sound dentin and less RT when Papacarie was used compared to Carisolv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The use of micro-CT has been increased in dental research on the validity for in vitro caries detection in permanent and in primary teeth. 15,[27][28][29][30] Previous studies reported that a significantly higher agreement was obtained by observers with micro-CT images. 13,14 It is important to emphasize that caries misdiagnoses in such cases can lead to unnecessary invasive treatments.…”
Section: Discussionmentioning
confidence: 95%
“…The use of micro-CT has been increased in dental research on the validity for in vitro caries detection in permanent and in primary teeth. 15,[27][28][29][30] Previous studies reported that a significantly higher agreement was obtained by observers with micro-CT images. 13,14 It is important to emphasize that caries misdiagnoses in such cases can lead to unnecessary invasive treatments.…”
Section: Discussionmentioning
confidence: 95%
“…Neves et al 10 evaluated nine carries removal methods with micro-CT. Their results were similar to ours in that the residual dentin mineral density was higher after traditional caries removal than after chemo-mechanical caries removal. Furthermore, AlHumaid et al 27 compared the removed tissue volume and mineral density of remaining dentin by using X-ray microtomography after caries removal with Papacarie and Carisolv TM . Compared with Carisolv TM , the use of Papacarie caused less tissue removal and produced healthier dentin.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is gaining increasing popularity in dental research. 10,[24][25][26] Studies have been published comparing caries removal method efficacies by means of micro-CT. 27,28 However, to the best of our knowledge, Papacarie Duo has not been compared with conventional methods in terms of caries removal efficacy. Here, we evaluated dentin mineral density before and after caries removal with the traditional caries removal technique and Papacarie Duo method, with or without the use of caries detection dye.…”
Section: Introductionmentioning
confidence: 99%
“…Teeth were scanned with μCT before and after the application of Carisol and Papacarie, to compare dentin mineral density (DMD) and removed tissue (RT) volume. It was observed that Papacarie resulted in higher DMD, a greater volume of dentin and less RT compared to Carisol (79).…”
Section: Restorative Treatment Applicationsmentioning
confidence: 99%